The paradox of islamic finance: How shariah scholars reconcile religion and capitalism - Calder, Ryan (Princeton Princeton University Press, 2024)
How the booming Islamic finance industry became an ultramodern hybrid of religion and marketsIn just fifty years, Islamic finance has grown from a tiny experiment operated from a Volkswagen van to a thriving global industry worth more than the entire financial sector of India, South America, or Eastern Europe. You can now shop with an Islamic credit card, invest in Islamic bonds, and buy Islamic derivatives. But how has this spectacular growth been possible, given Islam's strictures against interest? In The Paradox of Islamic Finance.